2013
DOI: 10.3892/mmr.2013.1654
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of plasminogen activator activity and expression by cyclic mechanical stress in rat mandibular condylar chondrocytes

Abstract: To investigate the mechanism of cartilage degradation induced by overloading in the temporomandibular joint (TMJ), the effect of cyclic mechanical compressive stress on the activity of plasminogen activator (PA) and the expression of the predominant components of the PA system were analyzed in cultured mandibular condylar chondrocytes (MCCs) in rats. MCCs were exposed to cyclic mechanical compressive stress (2000, 4000 and 6000 µ strain) at 0.5 Hz by a four‑point bending system. The activity of PA was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…SerpinE1 −/− mice display altered clot lysis [49], whilst SerpinE2 −/− mice display neurological abnormalities and males are infertile [50,51]. As with the clade A serpins, both SerpinE1 and SerpinE2 are induced by pro-inflammatory cytokines in chondrocytes [52][53][54] and SerpinE1 has been shown to be induced by both mechanical loading and fluid shear stress [55,56]. In OA, some studies have observed decreased levels of both SerpinE1 [57] and SerpinE2 [21] in the cartilage, perhaps suggesting an increased proteolytic load.…”
Section: Clade Eplasminogen Activator Inhibitor-1 and Proteinase Nexin-1mentioning
confidence: 99%
“…SerpinE1 −/− mice display altered clot lysis [49], whilst SerpinE2 −/− mice display neurological abnormalities and males are infertile [50,51]. As with the clade A serpins, both SerpinE1 and SerpinE2 are induced by pro-inflammatory cytokines in chondrocytes [52][53][54] and SerpinE1 has been shown to be induced by both mechanical loading and fluid shear stress [55,56]. In OA, some studies have observed decreased levels of both SerpinE1 [57] and SerpinE2 [21] in the cartilage, perhaps suggesting an increased proteolytic load.…”
Section: Clade Eplasminogen Activator Inhibitor-1 and Proteinase Nexin-1mentioning
confidence: 99%
“… N. Hichijo et al 2014 [ 4 ] In vivo 14 rats CG (7) EG (7) Functional loading: CG (normal diet) EG (soft diet) Cellular response and condyle structure: Cartilage thickness, IGF-1r expression EG: reduction of the cartilage thickness, and reduction of IGF-1r immune positive cells A decrease in masticatory demand during the growth period leads to insufficient mandibular development, decreasing the IGF-1r expression and cartilage thickness. W. Chen et al 2013 [ 2 ] In vitro Rats Isolated mandibular cartilage cells Dynamic compressive loading: CG (unloaded) EG (2000, 4000, 6000 μ strain for 6,12 and 24 h) EG1–9 Cellular response: Collagen and proteoglycan synthesis plasminogen activator (PA) activity EG 2000 and 4000: increase of Collagen and proteoglycans synthesis, and low PA activity EG 6000: decrease of proteoglycans and collagen synthesis and increase of PA activity Mechanical overload upregulated PA activity, providing a proteolytic environment of extracellular matrix components and contributing to cartilage degradation in TMJ osteoarthritis. D. Yu et al 2007 [ 1 ] In vivo 100 rats CG (50) EG (50) Functional loading: CG 1–5 (soft diet during 6,12,24 and 48 h and 9 days) EG 1–5 (hard diet during 6,12,24 and 48 h and 9 days) Cellular response: Immunohistochemical (IHC) analysis and western blot (WB) aggrecanase-1 and TIMP-3 EG (only on IHC, no difference was found on WB) aggrecanase-1 was higher at 12 and 24 h, after 48 h, there was no difference.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of the ECM involves the production of collagen fibers, proteoglycans, and aggrecans, and its degradation is caused by the action of enzymes such as aggrecanases and matrix metalloproteinases (MMPs). An important mechanism responsible for the regulation of ECM turnover in the TMJ is mechanical loading [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of mechanical stress on mandibular cartilage and chondrocytes has been investigated both in vitro and in vivo. Due to excessive mechanical stress, activation of the plasminogen activator system is induced, which can lead to proteolysis of ECM components [32]. However, the causal relationship between TMJ OA, facial asymmetry, and masticatory muscle overuse is not yet clear.…”
Section: Excessive Mechanical Stress and Malocclusionmentioning
confidence: 99%